Measures of firm performance and concentration: Stylized facts and a dilemma of data reproduction - Jan Weber; Ellis Scharfenaker (The University of Utah, Department of Economics, 2022)
Economists and policy makers have used the increase in the concentration of return on invested capital (ROIC) in publicly-traded US firms over the last decades as evidence for the decline of competitiveness in the broader economy. Principle support for this claim is a graph presented by the Council of Economic Advisors (CEA, 2016) that reproduces data from the McKinsey and Company's book on Corporate Valuation. We demonstrate that the key findings associated with the evolution of the ROIC cannot be broadly reproduced using Compustat data and established accounting measures and calculations. Further, we find that the ad-hoc selection of firms used in the study can result in discarding nearly 90% of the available firm-level data. Rather than rejecting the results of the CEA altogether, we correct their story in its core statement and contribute to it by presenting the full dataset. As the CEA finds an increasing concentration in the upper end of the distribution, we find increasing concentration for low-ROIC firms. The concentration increase for the top 10% of firms that we find is lower than the one presented by the CEA and limited to large firms. The presented results in this paper are satisfyingly robust, regardless of whether we use only 'large firms' or the complete, available sample of data. We conclude that the original story of an increased concentration of ROIC must be handled with care. Drawing macroeconomic conclusions from firm-level data should include all available and relevant information.
Keywords: 330; Unternehmenserfolg; Wettbewerb; Messung; Statistische Daten; Theorie